Phenomenological hysteretic model for corroded reinforcing bars including inelastic buckling and low-cycle fatigue degradation. (August 2015) - Kashani, Mohammad M.; Lowes, Laura N.; Crewe, Adam J.; Alexander, Nicholas A.
Highlights: Hysteretic behaviour of corroded bars. Analytical modelling of post-yield buckling of corroded bars. Influence of corrosion on low-cyclic fatigue behaviour of reinforcing bars. Modelling the impact of corrosion on cyclic degradation of corroded bars. Abstract: A new phenomenological hysteretic model for reinforcing bars with and without corrosion damage is presented. The model simulates buckling of reinforcement, deterioration in post-buckling compressive strength due to strain history and the impact of low-cycle fatigue on tension response. The model, for uncorroded reinforcing bars, is calibrated using data from numerical simulations and corrosion damage parameters are calibrated using experimental data. The model is evaluated using a comprehensive experimental data set, and the results show that the model is in a good agreement with the data.